2017
DOI: 10.1002/osp4.91
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the efficacy of omega-3 supplementation on liver steatosis and carotid intima-media thickness: a pilot study

Abstract: SummaryPurposeTo determine the effects of omega‐3 supplementation on liver fat and carotid intima–media thickness (IMT) and to assess accuracy of ultrasound (US) for grading liver steatosis.Materials and MethodsIn this one‐way crossover pilot study, we assigned children with obesity and liver steatosis to receive 1.2 g daily of omega‐3 supplementation vs. inactive sunflower oil for 24 or 12 weeks. Liver fat content was assessed by magnetic resonance spectroscopy (MRS), magnetic resonance imaging (MRI) and US, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Several studies also reveal a relationship between dietary intake of omega-3 PUFAs and a decrease in atherosclerotic calcifications, EPA and DHA inhibiting calcification in vivo [10,[55][56][57]. Omega-3 supplementation decreased carotid IMT in children with obesity and liver steatosis [58] and in haemodialysis patients [59].…”
Section: Fatsmentioning
confidence: 99%
“…Several studies also reveal a relationship between dietary intake of omega-3 PUFAs and a decrease in atherosclerotic calcifications, EPA and DHA inhibiting calcification in vivo [10,[55][56][57]. Omega-3 supplementation decreased carotid IMT in children with obesity and liver steatosis [58] and in haemodialysis patients [59].…”
Section: Fatsmentioning
confidence: 99%
“…Hepatic steatosis may influence the bioavailability of polyphenols 38–40. Thus, systemic diseases should also be influenced by the effects of polyphenols 41 42. A systematic review of resveratrol (a polyphenol) in adults demonstrated inconclusive effects on NAFLD 43 44…”
Section: Introductionmentioning
confidence: 99%